Know your numbers : little quick fix - Macinnes, John (London : Sage publication, 2018)
"Know Your Numbers: Little Quick Fix" by John Macinnes offers a concise and engaging guide to understanding the importance of numerical relationships in quantitative research. Designed for quick reference and easy comprehension, this full-color book uses a modern, visually appealing layout to make learning about numbers fun and accessible, not scary. It emphasizes not just how to work with numbers, but why understanding their relationships is crucial. The book's structure facilitates self-directed learning with features like 2-minute overview summaries, 3-second Q&A summaries, DIY tasks, checkpoints, and a final checklist, enabling students to quickly grasp key concepts and assess their progress. Macinnes' direct writing style and lack of fluff ensure that readers can efficiently find the information they need to overcome research hurdles, complete assignments, and ultimately succeed in their quantitative work.
Includes glossary.
Keywords: Mathematics; Statistics; Data analysis